Comparison of the effects of gemigliptin and dapagliflozin on glycaemic variability in type 2 diabetes: A randomized, open‐label, active‐controlled, 12‐week study (STABLE II study). Issue 2 (17th October 2019) - Kwak, Soo Heon; Hwang, You‐Cheol; Won, Jong Chul; Bae, Ji Cheol; Kim, Hyun Jin; Suh, Sunghwan; Lee, Eun Young; Lee, Subin; Kim, Sang‐Yong; Kim, Jae Hyeon
Abstract: Aims: The aim of this study was to compare the effect of gemigliptin, a dipeptidyl peptidase‐4 inhibitor, and dapagliflozin, a sodium glucose co‐transporter‐2 inhibitor, on glycaemic variability in type 2 diabetes patients. Materials and methods: In this randomized, blinded end point, multicentre clinical trial, we enrolled 71 patients with type 2 diabetes who were inadequately controlled with metformin alone or were drug naïve. The participants were randomized to receive gemigliptin 50 mg (n = 35) or dapagliflozin 10 mg (n = 36) daily for 12 weeks. Glycaemic variability was estimated by mean amplitude of glycaemic excursions (MAGE), standard deviation (SD) and coefficient of variation (CV) using a 6‐day continuous glucose monitoring system. The primary efficacy endpoint was change in MAGE after 12 weeks compared to baseline. Results: Intergroup differences in baseline characteristics were not significant. The adjusted mean change (± standard error) in MAGE after 12 weeks in the gemigliptin and dapagliflozin groups was −27.2 ± 4.4 mg/dL and −7.9 ± 4.9 mg/dL, respectively. Between‐group comparisons showed a significantly larger reduction in MAGE in the gemigliptin group (−19.2 mg/dL; 95% CI, −31.3 to −7.2; P = .002). Measures of SD and CV also showed a significantly larger reduction in the gemigliptin group. Average glycaemic control, estimated by HbA1c, fasting glucose and safety profiles, was comparable between the two groups. Conclusions: Compared to dapagliflozin, gemigliptin significantly improved glycaemic variability, with similar glucose‐lowering efficacy and safety profiles in patients with type 2 diabetes who were inadequately controlled with metformin alone or were drug naïve.